Antimicrobial Resistance Genes, Cassettes, and Plasmids Present in Salmonella enterica Associated With United States Food Animals - McMillan, Elizabeth A.; Gupta, Sushim K.; Williams, Laura E.; Jové, Thomas; Hiott, Lari M.; Woodley, Tiffanie A.; Barrett, John B.; Jackson, Charlene R.; Wasilenko, Jamie L.; Simmons, Mustafa; Tillman, Glenn E.; McClelland, Michael; et al. (Frontiers in Microbiology, 2019)
The ability of antimicrobial resistance (AR) to transfer, on mobile genetic elements (MGEs) between bacteria, can cause the rapid establishment of multidrug resistance (MDR) in bacteria from animals, thus creating a foodborne risk to human health. To investigate MDR and its association with plasmids in Salmonella enterica, whole genome sequence (WGS) analysis was performed on 193 S. enterica isolated from sources associated with United States food animals between 1998 and 2011; 119 were resistant to at least one antibiotic tested. Isolates represented 86 serotypes and variants, as well as diverse phenotypic resistance profiles. A total of 923 AR genes and 212 plasmids were identified among the 193 strains. Every isolate contained at least one AR gene. At least one plasmid was detected in 157 isolates. Genes were identified for resistance to aminoglycosides (n = 472), β-lactams (n = 84), tetracyclines (n = 171), sulfonamides (n = 91), phenicols (n = 42), trimethoprim (n = 8), macrolides (n = 5), fosfomycin (n = 48), and rifampicin (n = 2). Plasmid replicon types detected in the isolates were A/C (n = 32), ColE (n = 76), F (n = 43), HI1 (n = 4), HI2 (n = 20), I1 (n = 62), N (n = 4), Q (n = 7), and X (n = 35). Phenotypic resistance correlated with the AR genes identified in 95.4% of cases. Most AR genes were located on plasmids, with many plasmids harboring multiple AR genes. Six antibiotic resistance cassette structures (ARCs) and one pseudo-cassette were identified. ARCs contained between one and five resistance genes (ARC1: sul2, strAB, tetAR; ARC2: aac3-iid; ARC3: aph, sph; ARC4: cmy-2; ARC5: floR; ARC6: tetB; pseudo-ARC: aadA, aac3-VIa, sul1). These ARCs were present in multiple isolates and on plasmids of multiple replicon types. To determine the current distribution and frequency of these ARCs, the public NCBI database was analyzed, including WGS data on isolates collected by the USDA Food Safety and Inspection Service (FSIS) from 2014 to 2018. ARC1, ARC4, and ARC5 were significantly associated with cattle isolates, while ARC6 was significantly associated with chicken isolates. This study revealed that a diverse group of plasmids, carrying AR genes, are responsible for the phenotypic resistance seen in Salmonella isolated from United States food animals. It was also determined that many plasmids carry similar ARCs.